Pt-anchored-zirconium phosphate nanoplates as high-durable carbon-free oxygen reduction reaction electrocatalyst for PEM fuel cell applications - Kumar, Sachin; Yoyakki, Athira; Pandikassala, Ajmal; Soni, Roby; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Commercially available platinum-supported carbon (Pt/C) catalysts are the most widely used oxygen reduction reaction (ORR) electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs). However, inadequate active triple-phase boundary formation and carbon oxidation in Pt/C during PEMFC operation shorten its lifetime and efficiency. In this direction, a new class of carbon-free electrocatalysts for ORR is prepared by dispersing Pt nanoparticles on ZrP (Zirconium phosphates) nanoplates. In one case (ZrP@Pt), the Pt nanoparticles are found to be closely distributed and completely covering the ZrP nanoplates, whereas in the second case (Pt/ZrP), the Pt nanoparticles selectively restrict dispersion along the edges of the support. ZrP as the support displays an intrinsic proton conductivity of approximate to 0.5 x 10(-4) S cm(-1) at 70 degrees C, with an activation energy (E-a) of 0.19 eV. Pt/ZrP shows better durability after 3000 start-stop cycles. The mass activity of Pt/ZrP is increased by 4.6 times compared to Pt/C, which exhibits a loss in mass activity by 1.37 times. The single-cell level validation of ZrP@Pt, Pt/ZrP, and Pt/C as the electrocatalysts in PEMFC at an operating potential of 0.60 V shows the achievable current densities of 0.600, 0.890, and 0.890 A cm(-2).
Keywords: carbon-free electrocatalysts; fuel cells; oxygen reduction reaction; zirconium phosphate